Head-Up Tilt Test in Risk Stratification of Patients with Hypertrophic Cardiomyopathy - Sediva, Hana; Hnat, T.; Bonaventura, J.; Slesarenko, J.; Veselka, J. (International Journal of Angiology, 2019)
Conflicting results have been published considering the role of head-up tilt test (HUTT) positivity as a prognostic factor in patients with hypertrophic cardiomyopathy (HCM). The relationship between HCM patients' genotype and their HUTT results has not been previously reported.The aim of this study was to evaluate patients with HCM and their HUTT results in regard to its value for outcome prediction and to investigate the relation of patients' genotype and their HUTT results.Seventy-four (51 ± 15 years; 42% women; median follow-up 72 months) HCM patients were divided into two groups based on their HUTT results and were retrospectively analyzed. In 67 (90.5%) subjects included in the analysis, next-generation sequencing-based genomic testing was performed. A composite end point of unexplained syncope, heart failure hospitalization, and death was defined.A total of 14 patients (18.9%) had positive HUTT (HUTT+), whereas 60 (81.1%) had negative HUTT (HUTT–). Except for the New York Heart Association functional class (p = 0.01), both groups had similar characteristics. Positive genotype was evenly distributed between the two groups. Composite end point occurred in 5 patients (35.7%) in HUTT+ group versus 14 (23.3%) patients in HUTT– group (p = 0.33).We did not find a relationship between HUTT results and long-term outcome. We found no association between HUTT results and genotype.
Keywords: hypertrophic cardiomyopathy; HCM; hypertrophic obstructive cardiomyopathy; HOCM; head-up tilt test; genotype; abnormal baroreflex